The significance of Cambro-Ordovician trilobites from the Kalladeina 1 drill hole, Warburton Basin, South Australia. Issue 4 (19th May 2017) - Sun, X. W.; Bentley, C. J.; Jago, J. B.
ABSTRACT: The significance of trilobites described from six cores from the Kalladeina 1 drillhole from the Warburton Basin, northeastern South Australia is discussed. The oldest are from a dark grey shale of Core 16 from a depth of 3453.7–3455.8 m; they are of possible early Drumian (Cambrian Series 3, middle Cambrian) age. The youngest come from a dark grey shale of Core 4 at a depth of 2017.2–2022.04 m. This fauna contains the trilobites Asaphellus ? sp., Yosimuraspis sp., Conophrys sp. and Protopliomerops ? sp. thus indicating a Tremadoc (earliest Ordovician) age. These are the youngest known trilobites from the Warburton Basin and the youngest known in South Australia.